Análise da decisão judicial no quadro da legisprudência: o diálogo das fontes do direito - Leticia Camilo dos Santos (2011)
The research context is related to the legitimacy crisis of legislation due to the poor quality of norms, as well as the decentralization of law-making activity for other spheres of power. This perspective raised inquires about current legal rationality especially its disregard for the process of creation of rules, considered a matter of politics. Alternatively, this research sustains an approach named legisprudence, a normative theory of legislation articulated to legal theory which deals with the study of the creation of law by the legislator, taking into account aspects of efficiency, effectiveness and acceptability. The duty to justify in order to create rules is presented as a condition of legitimacy and improvement of the democratic character of the system. The justification results of a dialogical process based on a practical rationality. Combined with realization of the dialogue of sources and participative discussion, it improves the possibility of making an informed choice context-related. In this way, the research highlighted the importance of rethinking the theory of sources, adopting a pluralist perspective that takes into account the social and historical complexity of law. The duty of dialogue of sources emerges from an adoption of a comprehensive and collaborative point of view by the legislator, which enables him to improve legislation in order to get a greater knowledge of the repertoire of possible normative contents diffuse in society. The consideration of the increasing intersection between systems of common law and civil law displays a positive support to the acceptance of theoretical and practical influences of non legislative sources in the constitution of law. The judicial decision reveals a potential repertoire of meanings linked to time dimension that must be considered by the legislator. The enhancement of legitimacy and quality of legislation can be operated by evaluation of legislation, and, mainly, they result from the responsive performance of the legislator. This rationality is focused on developing effective and efficient rules, as well as in ensuring a space of liberty for the subject autonomous development. This comprehension makes possible participative action in society and critical reflection over the role played by political institutions.